Low-dimensional HfS2 as SO2 adsorbent and gas sensor: effect of water and sulfur vacancies† - Kanhounnon, G. Wilfried; Badawi, MichaeL; Ouahrani, Tarik; Bouheddadj, Amina; Reda, M. Boufatah; Morales-Garcıa, Angel (My University, 2021)
First-principles based on density functional theory (DFT) calculations were performed to investigate the interaction of two-dimensional (2D) HfS2 with SO2, a harmful gas with implications for climate change. In particular, we describe the effect of water and sulfur vacancies on such interaction. The former promotes the physisorption of SO2, whereas the latter promotes its chemisorption with structural changes on the absorbing surface. The results show that both structures are exothermic to adsorb the SO2 molecules, but the adsorption type is different. The reaction of the stable structure in the presence of water with the sulfur oxides is a physisorption interaction that enhances the band gap value of the isolated monolayer. However, for the defective structure, we have a chemisorption interaction type, where the adsorption of SO2 molecules widens the band gap values. To understand this behavior, we used Bader charge calculations and the noncovalent interactions index. While the water enhances the charge transfer between the monolayer and the adsorbed gas, the results show, however, that the defective structure is a more favorable gas sensor due to the metallic edge of the active site.
Keywords: HfS2; SO2; water; gaz sensor; adosrption; DFT